Penguatan Industri Halal Melalui Women’s Entrepreneurship Pada Umkm Di Wilayah Pesisir Kota Bengkalis - Misdawita, Misdawita; Sari, Lapeti; Utami, Bunga Chintia (Jurnal Ilmiah Ekonomi Islam, 2023)
The halal industry has a strategic role in improving the economy. The halal industry contributes USD 3.8 billion to Indonesia's Gross Domestic Product (GDP) annually. Bengkalis Regency is one of the regencies in Indonesia that has great potential for the development of the halal industry in coastal areas, moreover according to 2020 data from the Central Statistics Agency, Bengkalis Regency has 6,354 MSMEs which is the second largest in Riau Province. In Indonesia, women's entrepreneurship is a valuable contributor to the renewal and development of the domestic economy. According to a statistical report from the Central Bureau of Statistics, out of 2 million micro business units, 40.8% are controlled by women. This study uses a binary logistic regression model to determine what factors influence the decision of women entrepreneurs to obtain halal certificates. The results of this study found that ownership of halal certificates in MSME women entrepreneurs in Bengkalis Regency was influenced by age, number of children under five, average monthly income and interaction variables between type and length of business. While the factors of education, labor, length of business, human capital, and business performance do not significantly influence the ownership of halal certificates in MSMEs in Bengkalis Regency.